Folkloriziranje plesnega izročila - Knific, Bojan (Etnolog. Nova vrsta (Ljubljana), 2010)
The article addresses the issues of the dance heritage's folklorisation. It draws attention to the fact that researches into and the use of the dance heritage do not pay much attention to the temporal and social perspectives, and that special importance is attributed to the spatial aspect, to which research, book publications and stage performances of folklore groups relate. The author also points out the differences between primary, secondary, and tertiary forms of the dance heritage, the differences between folk dance and folkloric dance, and concludes with a reflection on the Register of the Living Cultural Heritage, which is to include the dance heritage.
Keywords: ljudski plesi; folklorne skupine; folklorizem; plesna dediščina; Slovenia; Slovenija